Facing death: A phenomenological study on cancer patients’ experienced existential anxieties - samaneh hosseini; saeid Pournaghash; Masoud Gholamali Lavasani (مجله علوم روانشناختی, 2023)
Background: More than 25% of cancer patients experience moderate to severe levels of distress arising from awareness of existential issues. Existential experiences in adults with advanced cancer are dynamic situation that precedes the encounter with death. A question that has not been addressed in past researches, and this research aims to address it, is whether existential anxiety is experienced in the same way in all these patients and follows the same pattern. Aims: This study aims to identify the lived experience of cancer patients from existential anxiety and how to face them. Methods: The present study was conducted with a qualitative approach and with an experimental and interpretive phenomenological method in the field of cognitive anthropology.The statistical community included all cancer patients in Shiraz.From this population, based on porposive sampling method, twelve cancer patients who were homogeneous in terms of the severity of the disease and were only under palliative care due to the lack of response to treatment, were selected, and in order to understand their perspectives regarding their lived experience of existential anxieties a semi-structured interview was conducted with them. Results: The analysis of the interviews led to the extraction of 9 codes about existential anxieties, five of which (death, loneliness, responsibility, meaning of life, uncertainty) were in line with the findings of research conducted in other cultures, and the other four (spirituality, love, cancer, emotions, and feelings) were extracted in this study. Also, a triple pattern in facing these anxieties, acceptance and submission, conflict and ambivalence, and complete lack of acceptance was identified. Conclusion: The findings of this research highlight the necessity of using meaning-oriented interventions by health and clinical professionals, as well as training and preparing doctors to pay attention to the existential anxieties of patients, especially those who are in the end stage of life.